2000
DOI: 10.1074/jbc.275.14.10315
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Novel Family of C2H2 Zinc Finger Proteins Implicated in Transcriptional Repression Mediated by Chicken Ovalbumin Upstream Promoter Transcription Factor (COUP-TF) Orphan Nuclear Receptors

Abstract: Two novel and related C 2 H 2 zinc finger proteins that are highly expressed in the brain, CTIP1 and CTIP2 (COUP TF-interacting proteins 1 and 2, respectively), were isolated and shown to interact with all members of the chicken ovalbumin upstream promoter transcription factor (COUP-TF) subfamily of orphan nuclear receptors. The interaction of CTIP1 with ARP1 was studied in detail, and CTIP1 was found to harbor two independent ARP1 interaction domains, ID1 and ID2, whereas the putative AF-2 of ARP1 was require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
205
3
3

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 188 publications
(230 citation statements)
references
References 58 publications
12
205
3
3
Order By: Relevance
“…A similar sequence, GGCCAAGG, is contained in the immediate upstream region of the translation start site, perhaps suggesting promiscuity in response element recognition by Bcl11b. Although Bcl11b was initially characterized as a transcriptional repressor (Avram et al 2000;Avram et al 2002), previous studies have shown activation of transcription of a target gene in the context of T-cell activation (Cismasiu et al, 2006), similar to our results.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…A similar sequence, GGCCAAGG, is contained in the immediate upstream region of the translation start site, perhaps suggesting promiscuity in response element recognition by Bcl11b. Although Bcl11b was initially characterized as a transcriptional repressor (Avram et al 2000;Avram et al 2002), previous studies have shown activation of transcription of a target gene in the context of T-cell activation (Cismasiu et al, 2006), similar to our results.…”
Section: Discussionsupporting
confidence: 82%
“…CTIP2), that showed enriched expression in the striatum and was decreased in the brains of R6/1 transgenic mice (Desplats et al 2006). Bcl11b is a C 2 H 2 zinc finger DNA binding protein that has been shown to alter transcription in vitro by interacting with chicken ovalbumin upstream promoter transcription factor (COUP-TF) family members (Avram et al, 2000), or via a sequence-specific DNA binding element that is related to the canonical GC box (Avram et al, 2002). Bcl11b is a critical developmental protein.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, intermittent hypernasality was observed in both patients. BCL11A is a known interactor of COUP‐TF1 and COUP‐TF1 knockout in mice results in malformations of the glossopharyngeal ganglion (Avram et al, 2000, 2002; Qiu et al, 1997). In humans the glossopharyngeal nerve and ganglion are responsible for motor (stylopharyngeal) and sensory innervation of the upper pharynx, and parasympathetic innervation of the parotid gland (Sarrazin, Toulgoat, & Benoudiba, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to mediate its repressor function either directly via binding to a GC-rich consensus sequence (Avram et al, 2002), or via interacting with chicken ovalbumin upstream promoter-transcription factor nuclear receptors (Avram et al, 2000), binding with SIRT1 histone deacetylase (HDAC) (Avram et al, 2002;Senawong et al, 2003Senawong et al, , 2005 and nucleosome remodeling and HDAC complex (NuRD), one of the major transcriptional co-repressor complexes in mammalian cells (Cismasiu et al, 2005;Topark-Ngarm et al, 2006). Recently, the first evidence has been provided, that Bcl11b activates transcription of the interleukin 2 gene in stimulated CD4 þ T lymphocytes (Cismasiu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%